2018
DOI: 10.12688/f1000research.14777.1
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective review on minimally invasive technique via endoscopic thoracic sympathectomy (ETS) in the treatment of severe primary hyperhidrosis: Experiences from the National Heart Institute, Malaysia

Abstract: Background: Hyperhidrosis is due to the hyperactive autonomic stimulation of the sweat glands in response to stress. Primary hyperhidrosis is a common yet psychologically disabling condition. This study will describe our experience in managing hyperhidrosis via endoscopic thoracic sympathectomy (ETS). Methods: The information was obtained from the patient records from 1st January 2011 until 31st December 2016.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…2 In the study of Musa AF et al, one patient developed a rare complication in the form of bradycardia. 6 In our study 70% of group A and 75% of group B developed compensatory sweating and it was ranging from mild to severe degree. The same results was found in the study of Findikcioglu A et al, as 71.4% (17.9 severe degree) from the cautery group and 71.9% (18.8 severe degree) from the clipping group developed compensatory sweating and the difference between the 2 groups was statistically insignificant (P = 0.8).…”
Section: Discussionsupporting
confidence: 47%
“…2 In the study of Musa AF et al, one patient developed a rare complication in the form of bradycardia. 6 In our study 70% of group A and 75% of group B developed compensatory sweating and it was ranging from mild to severe degree. The same results was found in the study of Findikcioglu A et al, as 71.4% (17.9 severe degree) from the cautery group and 71.9% (18.8 severe degree) from the clipping group developed compensatory sweating and the difference between the 2 groups was statistically insignificant (P = 0.8).…”
Section: Discussionsupporting
confidence: 47%
“…Therefore, we suggest the number of location(s) involved in CS to be considered as a confounder to postoperative QOL for future research. The clinical implication of this study is that with the high incidence of CS reported in this study and our previous study, 17 which can be associated with the involvement of T2 resection, it may be proposed to our institute regarding reducing ETS surgery that involves T2 resection. This suggestion is backed by the literature, which claims that symptom resolution was not significantly different between T2-involved and T2-spared group, but incidence of CS was significantly higher in the T2-involved group 26,36 .…”
Section: Discussionmentioning
confidence: 57%
“…Besides, we could not yield a similar finding to those found in our previous study 17 as our sample size is relatively small compared to previous studies. Furthermore, as this study is a continuation of the previous study 17 , different study populations used in the different studies may explain variations in the results. However, we believe that more surgeries sparing T2 should be carried out in order for further analysis on such association to be done.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations